Prevalencia de Microfilaria immitis en Felis silvestris catus atendidos en la Casa Comunal Ana María de Olmedo, Durán. - Altamirano Arias, Esther Isabel (2019)
The objective of the current work was to determine the presence of Microfilaria immitis in cats brought for consultation to Casa Comunal Ana María de Olmedo located in Durán. The subjects of investigation were 100 cats that were addressed in the time period between October and November of 2018; blood processing through Woo test was used to detect the presence of the parasite. From 100 individuals, females represented the 70 % while the remaining 30 % were male. According to the age variable, those below two years of age were the most representative, occupying the 71 %. A tendency toward intradomiciliary habits was observed. At the same time, 84 % of the population was asymptomatic; although, the area was favorable for the development of the vector. Due to the lack of resources for the appropriate identification of dirofilariasis, there could probably be an under registration of the disease, which complicates the determination of its incidence, even knowing that the carrier vectors exist. According to Robertson (2000), even though the disease in cats was first described in 1921, its diagnosis is still hard to find; this occurs because of the lack of clinical signs, as patients tend to be asymptomatic, or the signs that can be mistaken with those of respiratory diseases. Complications can be attributed to the reduced parasite load, the singular physiopathology the cat presents, and the limitations attributed to the diagnostic tests currently available in our times.